THE GLASS BEADS FROM CHENQUE 1 OF SIERRA COLORADA 1 (SAC -1-1), SALITROSO LAKE BASIN (SANTA CRUZ PROVINCE). SMALL LARGE TEMPORAL INDICATORS - Hajduk, Adam (Instituto Nacional de Antropología y Pensamiento Latinoamericano, 2024)
The use of new Information Technologies and Communication to promote sharing, participationin The glass beads found at the Chenque 1 indigenous burial site Chenque 1 (SAC-1-1) are studied,which due to their characteristics would correspond to the mid-16th century. Their manufacturingtechniques are analyzed and a quote from a historical chronicle and some archaeological backgroundfrom relatable accounts from other sites in Argentina and southern Chile are mentioned. The advancesachieved by North American researchers in the identification and chronological valuation of someglass beads from the 16th century are considered.